2012
DOI: 10.1155/2012/468452
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Tumor Lysis Syndrome in a Patient with Advanced Gastric Adenocarcinoma: Case Report and Literature Review

Abstract: Tumor lysis syndrome (TLS) is characterized by hyperuricemia, hyperkalemia, hyperphosphatemia, and secondary hypocalcemia in patients with a malignancy. When these laboratory abnormalities develop rapidly, clinical complications such as cardiac arrhythmias, acute renal failure, seizures, or death may occur. TLS is caused by rapid release of intracellular contents by dying tumor cells, a condition that is expected to be common in hematologic malignancies. However, TLS rarely occurs with solid tumors, and here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 87 publications
4
48
0
Order By: Relevance
“…TLS mortality rate in hematological malignancies was found as 36.3% and mortality rate in solid tumors was found as 42.8%. 6 . In our study, common solid metastases are present in all solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…TLS mortality rate in hematological malignancies was found as 36.3% and mortality rate in solid tumors was found as 42.8%. 6 . In our study, common solid metastases are present in all solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning TLS in solid tumours, ‘bulky disease’ is defined as: (1) abdominal tumour mass greater than 10 cm, either the primary tumour, retroperitoneal nodes or single liver metastasis or (2) multiple liver metastases with two bigger than 5 cm 13. Also ‘extensive metastases’ are defined as producing organ enlargement 24. Known pretreatment risk factors for the development of TLS are high LDH, uric acid, azotaemia and creatinine 6.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous TLS has been described in solid tumors and hematological tumors [6, 7]. Saravu et al reported a case having MM with spontaneous TLS, following a compression fracture of the L2 vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of rasburicase starts within 4 h and uric acid normalized within 3-4 days. In patients with a prior history of glucose-6-phosphate dehydrogenase, rasburicase is contraindicated and allopurinol should be utilized instead of rasburicase [6, 12]. …”
Section: Discussionmentioning
confidence: 99%